Marketing hotels and tourism online : website : make your website engage, convert and get more direct bookings - Clayton, Ian R. ([Place of publication not identifed] : [publisher not identified], 2016)
You're the busy tourism professional, an owner/manager of a hotel, a tourism business or a destination authority, you're passionate about creating a meaningful experience for your guests. You also know the importance of having a solid online presence, using marketing to build your brand, but are feeling overwhelmed that there is too much to learn and you're not tech savvy enough to understand it all. That's because up until now, there has been a system that guides you through each step of the process simply showing you how to strategize and implement a marketing plan that will actually make your life easier while growing your business. In Marketing hotels and tourism online, you will discover: how to master online marketing to build your brand, how to set your marketing on autopilot so you can get back to taking care of your guests and how to find trustworthy marketing consultants and evaluate offers. Website is the first book in the series. It offers strategies to perfect your website messaging and build an effective sales system. Next is digital media followed by technology. The series offers practical advice that will get you inspired, focused and ready to take control of your online marketing in an ever changing tourism landscape.
Introduction -- Travel marketing then and now -- Your tourism marketing plan -- The keys to traffic -- Perfect your presence -- Web strategy process -- Site navigation and linking -- Blogging for travel -- Building and marketing 5 star reviews -- Hot buttons and videos -- Make your site mobile friendly -- Thank you for reading.
Marketing hotels and tourism online :, Marketing
Keywords: HOSPITALITY INDUSTRY -- MARKETING